High-density SNP genetic linkage map construction and quantitative trait locus mapping for resistance to cucumber mosaic virus in tobacco (Nicotiana tabacum L.) - Cheng, Lirui; Chen, Xiaocui; Jiang, Caihong; Ma, Bing; Ren, Min; Cheng, Yazeng; Liu, Dan; Geng, Ruimei; Yang, Aiguo (The Crop journal, 2019)
Genetic linkage maps are essential for studies of genetics, genomic structure, and genomic evolution, and for mapping quantitative trait loci (QTL). Identification of molecular markers and construction of genetic linkage maps in tobacco (Nicotiana tabacum L.), a classical model plant and important economic crop, have remained limited. In the present study we identified a large number of single nucleotide polymorphism (SNP) markers and constructed a high-density SNP genetic map for tobacco using restriction site-associated DNA sequencing. In 1216.30 Gb of clean sequence obtained using the Illumina HiSeq 2000 sequencing platform, 99,647,735 SNPs were identified that differed between 203 sequenced plant genomes and the tobacco reference genome. Finally, 13,273 SNP markers were mapped on 24 high-density tobacco genetic linkage groups. The entire linkage map spanned 3421.80 cM, with a mean distance of 0.26 cM between adjacent markers. Compared with genetic linkage maps published previously, this version represents a considerable improvement in the number and density of markers. Seven QTL for resistance to cucumber mosaic virus (CMV) in tobacco were mapped to groups 5 and 8. This high-density genetic map is a promising tool for elucidation of the genetic bases of QTL and for molecular breeding in tobacco.